Memorias sobrevivientes: el álbum familiar en tres obras artísticas sobre la desaparición (Marcelo Brodsky, Gerardo Dell´Oro, Lucila Quieto) - Florencia Larralde Armas (Les Cahiers ALHIM)
In this article we will discuss three series of artistic photographs exhibited at the Museum of Art and Memory of the city of La Plata, Argentina. They make different uses of family albums to talk about the missing, abducted by Argentina's military dictatorship. We are interested problematize these photographic works in relation to the idea of « survivor memory », because in principle these samples share the key feature being developed by their families, they also have to photography as a profession. The series of Marcelo Brodsky, Gerardo Dell’Oro and Lucila Quieto, addressing images of happy past and through words and artistic operations reformulate these photographs. We want to ask what new senses open from these samples, and although each found their diversity and multiplicity, one thing they all share is a necessity and reaffirmation of the ties and also a reaffirmation of the senses with the which were produced these images photos from family archives.